Flying cars and hyperloops: A glimpse into the future sustainable vehicles - Hariram, Nediyirippil Prakasan; Megalingam, Arumugampillai; Sudhakar, Kumarasamy (Elsevier Ltd, 2025)
Transportation systems significantly impact the environment, necessitating urgent innovations to mitigate their adverse impacts. This paper presents a comprehensive review of emerging technologies with the potential to revolutionize green mobility across all major sectors: road, rail, water, and air. Key advancements, including electric propulsion, autonomous vehicles, aerial transport (flying cars), and underground systems (hyperloops), are analyzed for their strength and weaknesses. Additionally, the social and environmental implications of these future vehicles are examined. With a focus on sustainability and emissions reduction, this paper aligns with global efforts towards cleaner transportation and climate change mitigation. This approach goes beyond traditional reviews by providing a holistic view of future sustainable transportation systems. By synthesizing current advancements and addressing key challenges, this study offers critical insights to inspire researchers, engineers, and policymakers to develop resilient, sustainable transportation systems for a cleaner and greener future.